1978
DOI: 10.1063/1.862107
|View full text |Cite
|
Sign up to set email alerts
|

Initial value problem for Rayleigh–Taylor instability of viscous fluids

Abstract: The initial value problem associated with the development of small amplitude disturbances in Rayleigh–Taylor unstable, viscous, incompressible fluids is studied. Solutions to the linearized equations of motion which satisfy general initial conditions are obtained in terms of Fourier–Laplace transforms of the hydrodynamic variables, without restriction on the density or viscosity of either fluid. When the two fluids have equal kinematic viscosities, these transforms can be inverted explicitly to express the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…X), and recent surveys of previous work are given by Sharp (1984) and Kull (1991). Many of the analyses (e.g., Bellman andPennington, 1954, andMenikoff et al, 1978) have focused on the initial small-amplitude growth, where linearized equations are appropriate. One approach for examining the nonlinear effects of large amplitude is direct numerical simulation, e.g., Harlow and Welch (1966) and Tryggvason (1988), or through boundaryintegral computations, e.g., Baker and Meiron (1984), and Newhouse and Pozrikidis (1990).…”
Section: Introductionmentioning
confidence: 99%
“…X), and recent surveys of previous work are given by Sharp (1984) and Kull (1991). Many of the analyses (e.g., Bellman andPennington, 1954, andMenikoff et al, 1978) have focused on the initial small-amplitude growth, where linearized equations are appropriate. One approach for examining the nonlinear effects of large amplitude is direct numerical simulation, e.g., Harlow and Welch (1966) and Tryggvason (1988), or through boundaryintegral computations, e.g., Baker and Meiron (1984), and Newhouse and Pozrikidis (1990).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, as had been found in the study of related problems [3][4][5][6][7][8], the equation of motion of the free surface exhibits a " memory " effect of the free surface velocity. …”
mentioning
confidence: 79%
“…While this representation has been used more or less explicitly in several previous studies [2,[5][6][7], it has never been discussed in the detail desirable. Our reasons for discussing this matter are threefold.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This survey showed that the Rayleigh-Taylor instability exhibits essentially different behavior above and below a certain critical wavenumber k c . Menikoff et al 19 studied the IVP problem associated with the development of small amplitude disturbances in Rayleigh-Taylor unstable, viscous, incompressible fluids. In addition to normal modes, a set of continuum modes, not treated explicitly in the literature, makes an important contribution to the development of the fluid motion.…”
Section: Introductionmentioning
confidence: 99%